Faktor-Faktor yang Mempengaruhi Kualitas Pelayanan Publik pada Kantor Kelurahan Klabinain Aimas Kabupaten Sorong Provinsi Papua Barat - Pratiwi, Ida Ayu Putu Cindi; Spalanzani, Widya; Saputra, Yayan; Rosihan, Rifda Ilahy; Kumalasari, Ratih; Masjuli, Masjuli (Journal of Industrial and Engineering System, 2022)
Human resources (HR) referred to as the spearhead to achieve goals in a government, as well as the facilities used in carrying out public services. However, HR and facilities at the Klabinain Aimas Village office not effective so that they have not been able to carry out public services properly. This research aims to determine whether or not the influence of HR and facilities on the quality of public services at the Klabinain Aimas Village Office. The sample in this study amounted to 123 people with the sampling technique using simple random sampling. Hypothesis testing using classical assumption test and simple regression analysis using the IBM SPSS Ver 26 application to determine the contribution of the independent variable to the dependent variable at the 95% trend level (α = 0.05). The results are there is no positive and significant influence between HR on public services at the Klabinain Aimas Village office. There is no positive and significant effect between facilities and public services at the Klabinain Aimas Village office, and there is a significant effect between HR and facilities if tested simultaneously on public services at the Klabinain Aimas Village office.